Education on waste management in Kelurahan 13 Ulu, Palembang City - Dewi Pujiana; Aurellia Zafirah Abeer Jacinda; Ayu Edayati; Ayu Febriani; Bambang Sugiarto; Dwi Sepdianti; Mutiara Florensa; Naswa Azzahra; Novi Ridianti; Putri Utami; Salma Az-Zahra Abdindra (Universitas Muhammadiyah Magelang, 2024)
A serious problem often faced in Kelurahan 13 Ulu, involving RT 13, RT 14, RT 15, and RT 16, is waste management. The community's level of knowledge regarding waste management in this area is still low, exacerbated by a lack of supporting facilities that worsen environmental conditions. Therefore, this activity aims to address these issues by educating residents on the importance of cleanliness, proper waste separation, and utilizing waste for economic value. The method used involves preparation, implementation, and evaluation stages, including installing signs prohibiting waste dumping at various locations where waste accumulates. The positive impact of this activity includes increased awareness of cleanliness, improved understanding of waste sorting, and knowledge of its benefits. Additionally, residents are educated on the 3R principle (Reduce, Reuse, Recycle) for waste processing, leading to a better understanding of waste management, particularly in separating organic and inorganic waste.